"Dragon's Lair" Feng Shui Landscape Pattern and Its Interpretation in the Context of Urban Planning Practice in Southern Primorye. Issue 2 (March 2021) - Kazantsev, P; Marus, Y; Movchan, E
Abstract: The article discusses the architectural and urban aspect of "Feng Shui" method for assessing landscape and climatic conditions, and the possibility of its use in the South of the Russian Far East. Following the "Feng Shui" rules, setting the distribution of energy on certain landscapes, we are dealing with the results of a comprehensive assessment of landscape, climate and other aerial characteristics. The overall landscape and climate characteristics of the territory (recorded in our case in the "Sha" or "Qi" energy distribution features) are not sufficient for the choice of certain urban planning techniques. In this regard, the "dragon's liar" landscape situation and the monsoon climate province climatic factors interaction analysis is of practical interest also for regional urban planning. The article assesses the influence of landscape and climatic factors on the formation of comfortable conditions within the "Dragon's Lair". In relation to the local landscape and climatic conditions of the Vladivostok agglomeration shown, that the method of finding out the landscape patterns conformed to "Dragon's Lair" characteristics usage practicability in the region is related to the such landscape morphotypes frequence and the annual wind and insolation regimes characteristics common for different areas. Under these conditions it is possible to identify the most comfortable terrain areas at the stage of developing an urban or rural settlement master plan, according to the topography analysis.